Cefepime/clindamycin vs. ceftriaxone/clindamycin for the empirictreatment of poisoned patients with aspiration pneumonia - Talaie, H.; Jabari, H. R.; Shadnia, S.; Pajouhmand, et al., A. (Acta Biomedica Atenei Parmensis, 2008)
Different antimicrobial treatments have proved to be effective in patients with aspiration pneumonia. However, resistant bacterial strains are commonly observed in hospital settings challenging the empirical treatment of these patients. In this study, we aimed to compare the efficacy of cefepime/clindamycin and  ceftriaxone/clindamycin for empiric therapy of poisoned patients with aspiration pneumonia. In an open, randomized, prospective design, 140 consecutive patients aged more than 13 years, with radiographic signs of infiltration in chest radiography and dullness on percussion or pulmonary rales or ronchi in combination with at least two of the following clinical criteria were considered as eligible: fever ≥ 37oC (axillary), or hypothermia < 35°C (axillary) and leukocytosis (> 10 cells/mm3), or leukopenia (< 3,000 cells/mm3), a left-shift of > 10%, or purulent sputum or secretion from trachea or bronchi. Participants received intravenously either ceftriaxone 1 g q12 h and clindamycin 900 mg q8 h (group 1) or cefepime 1 g q12 h and clindamycin 900 mg q8 h (group 2). On day 5 of treatment, the number of improved/cured patients was not different between groups (OR 0.86; 95%CI 0.24 to 2.90) nor at 14 days of the study (OR 0.66; 95%CI 0.12 to 3.29). Six patients died in group 1 and 5 in group 2 (RR 0.83; 95%CI 0.28 to 2.46). In conclusion, efficacy of empiric treatment of poisoned patients with aspiration pneumonia with ceftriaxone/clindamycin was comparable to treatment with cefepime/clindamycin.